Sylvester and the magic pebble - Steig, William, 1907-2003 (Simon and Schuster Books for Young Readers, 2005)
In a moment of fright, Sylvester the donkey asks his magic pebble to turn him into a rock but then can not hold the pebble to wish himself back to normal again.